DRAMATURGI: PENCITRAAN PRABOWO SUBIANTO DI MEDIA SOSIAL TWITTER MENJELANG PEMILIHAN PRESIDEN 2014 - Fitri, Ainal (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:Twitter social media becomes one of the means to make a positive self-image to public. It was also made by a presidential candidate ahead of the 2014 elections. By using the dramaturgical theory of Erving Goffman, this article tries to analyze the dramaturgy from front stage and backstage conducted by a presidential candidate Prabowo as Indonesia via his Twitter account @Prabowo08. From the analysis it can be seen that Prabowo perform imaging with the aim to bring out the positive side of himself-so gain the sympathy of the people, but tend to cover issues regarding his oblique.